2018
DOI: 10.1016/j.heliyon.2018.e00715
|View full text |Cite
|
Sign up to set email alerts
|

The association between the perception of crime and walking in gated and non-gated neighbourhoods of Asian developing countries

Abstract: It has been reported in the literature that the perception of crime at the neighbourhood level inversely affects the walking behaviour of individuals. On the other hand, the gated neighbourhoods are considered safe from crime, however, there is a lack of research on the association of the perception of crime and walking in gated neighbourhoods. Therefore, the objectives of the study reported in this paper were to investigate the association between the perception of crime and walking in gated and non-gated nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…It was found that the most important elements in urban design contributing to that sense of identity, of belonging and of a comfortable urban life are physical settings, including landmarks. To examine how the urban form might impact the social aspect of residents' lives, a number of everyday services and facilities can be selected for further scrutiny (Dempsey et al, 2009;Rafiemanzelat, 2016;Gul et al 2018). Researchers such as Salah and Ayad, 2018;Indjy, (2016) and Dempsey et al (2009), whose identified these services and facilities to include both "key" services used by residents on a regular basis and other services that are used less often, but which are nevertheless found within the urban community.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the most important elements in urban design contributing to that sense of identity, of belonging and of a comfortable urban life are physical settings, including landmarks. To examine how the urban form might impact the social aspect of residents' lives, a number of everyday services and facilities can be selected for further scrutiny (Dempsey et al, 2009;Rafiemanzelat, 2016;Gul et al 2018). Researchers such as Salah and Ayad, 2018;Indjy, (2016) and Dempsey et al (2009), whose identified these services and facilities to include both "key" services used by residents on a regular basis and other services that are used less often, but which are nevertheless found within the urban community.…”
Section: Introductionmentioning
confidence: 99%
“…Few empirical studies have shown the level of safety among residents from diverse socioeconomic and demographic backgrounds in the context of gated communities (Ferraro, 1995;Makinde, 2020a). Alohan and Ogedengbe (2018) looked at the comparative study of the influence of gated and non-gated residential estates on property values in Edo State in Nigeria whilst Gul et al (2018) analysed the association between the perception of crime and walking in gated and non-gated neighbourhoods of Asian developing countries. In essence, limited studies alluded to the area of the perception of residents' safety in the context of gated communities.…”
Section: Reviewing Past Literaturementioning
confidence: 99%
“…The physical characteristics may sometimes be in the form of barriers and enclosures, or demarcation, which are used to define members and outsiders (Gul et al, 2018). Though urban culture encourages individualism and anonymity, the concern for the safety of lives and property serves as a centripetal force and the basis for regrouping in residential neighbourhoods (Williamson, 2003).…”
Section: 10 Introductionmentioning
confidence: 99%
“…There are positive associations found in the literature between the presence of sidewalks [13], the presence of footpaths [14], and accessibility to opportunity for activity [15] with recreational walking. Some studies have failed to show such relationships between recreational walking and street connectivity [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…While several researchers have investigated the correlation between walking and street connectivity, no studies have investigated the effects of a new form of neighborhoods, the gated neighborhoods (GC's), which are growing very fast all over the world [14,15,16]. The GC's are generally developed to serve one of the three purposes; prestigious GC's to house the upper class, lifestyle GC's to keep upper-middle class physically active, and security zone GC's [14,17,18].…”
Section: Introductionmentioning
confidence: 99%